2017
DOI: 10.1590/s1679-45082017ao3894
|View full text |Cite
|
Sign up to set email alerts
|

Interventions of the clinical pharmacist in an Intermediate Care Unit for elderly patients

Abstract: Objective To discuss the role of the clinical pharmacist in hospital care of critical elderly patients.Methods Critical patients aged 60 years and over admitted by the clinical staff to an Intermediate Care Unit were followed-up for 4 months regarding their drug therapies. Medical prescriptions were reviewed daily on the basis of patients’ clinical conditions, with the view to identify opportunities for optimization of drug therapies, contributing to safer prescribing, reduced discomfort and correct and ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 16 publications
4
14
1
14
Order By: Relevance
“…In general, the acceptance of pharmaceutical interventions in this study, when compared to those of another Brazilian organization, (20) were discrepant, since in this study the authors observed a lower intervention acceptance rate. Such findings may be partially attributed to the fact of communication of the pharmaceutical interventions being documented in the medical records, and for the time interval determined for reevaluation by the pharmacist.…”
Section: ❚ Discussioncontrasting
confidence: 83%
“…In general, the acceptance of pharmaceutical interventions in this study, when compared to those of another Brazilian organization, (20) were discrepant, since in this study the authors observed a lower intervention acceptance rate. Such findings may be partially attributed to the fact of communication of the pharmaceutical interventions being documented in the medical records, and for the time interval determined for reevaluation by the pharmacist.…”
Section: ❚ Discussioncontrasting
confidence: 83%
“…As doenças crônicas são apontadas como os principais fatores de risco para desenvolvimento de doenças cardiovasculares (21,22,23,24), as quais constituem as principais causas de morte no mundo nos últimos 15 anos (25). A ocorrência de múltiplas condições clínicas também é a principal causa de polimedicação, pois para cada uma destas enfermidades, torna-se necessária a associação de fármacos para se alcançar um tratamento farmacológico eficaz, situação que está diretamente relacionada ao aumento da probabilidade de PRM (24,26,27).…”
Section: Resultsunclassified
“…Na fitoterapia, exigirá do farmacêutico conhecimento científico, popular e tradicional do uso de plantas medicinais e fitoterápicos, como também das várias formas de uso, de forma a integrar os diferentes saberes, profissionais e usuários, buscando avaliar e garantir a segurança, a eficácia e a efetividade do uso desses recursos terapêuticos (Brasil, 2012). A prática da atenção farmacêutica tem se mostrado de uma expressiva eficácia, tendo impactado na diminuição de agravos de saúde e internações por se tratar de um esquema arquitetado clinicamente de forma excepcionalmente personalizado ao paciente e que busca no profissional atuante o domínio dos dados reais apurados em literaturas para uma expressivo ação direcionada aos grupos mais susceptíveis as problemáticas relacionadas aos agravos e seus principais causadores (Viana, Arantes & Ribeiro, 2017). Considerando as variáveis que envolvem a hipertensão e o atendimento ao idoso, há a necessidade de vários profissionais atuando em conjunto para tratá-lo, o farmacêutico pode atuar de diversas maneiras para auxiliar o paciente: facilitador da adesão ao tratamento, auxiliar o paciente junto aos fatores de risco (obesidade, tabagismo, ingestão de sal colesterol elevado), auxiliar do prescritor a controlar o tratamento, agente elaborador de campanhas junto à comunidade, auxiliar para amenizar os fatores que dificultam o tratamento, articulação com outros profissionais da saúde e descrição de reações adversas (WHO, 2014;Pelentir, Deuschle & Deuschle, 2015).…”
Section: Atenção Farmacêutica No Uso Das Plantas Medicinais Com Ação Anti-hipertensiva Direcionada à Idososunclassified